Percepción sobre violencia obstétrica en mujeres gestantes de primer y segundo trimestre (2023)
Objective: Describing the perception of obstetric violence in women during the first and second trimesters of gestation in Neiva. Methodology: The descriptive qualitative approach was implemented so that it allowed us to know women's perceptions about obstetric violence during their first and second trimesters of pregnancy. In order to do so, in-person and open interviews were addressed with the objective of collecting information and detailed data that subsequently was transcribed and coded into categories and subcategories. Results: Diverse approaching strategies were implemented with the pregnant women, such as visual divulge, preparation courses for maternity and safe parenting, and phone calling. The sample was obtained implementing convenience sampling, which led to reaching data saturation. Among the results, it was noticed that all the participants lived in socioeconomic status 1 (the lowest grade) and were affiliated to the subsidized Healthcare system. Despite the fact that more than half of the interviewees had completed their secondary education, there was evidence of a generalized lack of knowledge about obstetric violence. It was possible to establish categories on the perception, association, types and forms of obstetric violence, which subsequently led to the creation of subcategories according to the manifestations of the gestants. Conclusion: Obstetric violence is a complex and multifaceted problem that can be difficult to address. Such difficulty comes from the fact that the target population lacks knowledge and understanding of this subject. It is important to communicate about obstetric violence and work to increase public awareness so that this problem can be effectively addressed and prevented.